Terminator field-aligned current system: Its dependencies on solar, seasonal, and geomagnetic conditions. (November 2017) - Zhu, L.; Schunk, R.W.; Eccles, V.; Scherliess, L.; Sojka, J.J.; Gardner, L.
Abstract: A new field-aligned current system in the high-latitude ionosphere, the terminator field-aligned currents, was recently discovered by Zhu et al. (2014). A series of modeling, observational, and theoretical studies need to be performed in order to get a full picture of the behavior and properties of this newly discovered current system, understand the underlying physics, and explore its effects on the electrodynamics and plasma dynamics of the high-latitude ionosphere. As a first step in this direction, we performed a systematic study on the seasonal, solar, and geomagnetic dependencies of the general properties of the terminator field-aligned currents. The study was conducted by using a physics-based data assimilation model, Ionospheric Dynamics and Electrodynamics Data Assimilation (IDED-DA) Model, with the ingestion of observational data. Highlights: During summer (winter), the currents are mainly downward (upward) and appear at early (later) UT time. A higher solar flux during summer can lead to the currents with a wider width and an elongated extension along the terminator. The currents are not sensitive to geomagnetic conditions.